2006
DOI: 10.1002/jso.20569
|View full text |Cite
|
Sign up to set email alerts
|

Staging of esophageal carcinoma: Length of tumor and number of involved regional lymph nodes. Are these independent prognostic factors?

Abstract: A revision of the TNM classification for esophageal carcinoma should subdivide the pN1-category according to the number of LNM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
1
19

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 33 publications
7
103
1
19
Order By: Relevance
“…Within pelvic and periaortic lymphadenectomy, the number of LNs assessed depends on the attitude of the surgeon and on the accuracy of the pathological evaluation undertaken. The ratio metastatic to examined LNs may obviate the possible confounding effect [18]. Nigro et al showed that patients with an LNR < 0.1 fared significantly better than those who had an LNR > 0.1 [19].…”
Section: Resultsmentioning
confidence: 99%
“…Within pelvic and periaortic lymphadenectomy, the number of LNs assessed depends on the attitude of the surgeon and on the accuracy of the pathological evaluation undertaken. The ratio metastatic to examined LNs may obviate the possible confounding effect [18]. Nigro et al showed that patients with an LNR < 0.1 fared significantly better than those who had an LNR > 0.1 [19].…”
Section: Resultsmentioning
confidence: 99%
“…In a study of 2,597 patients from the SEER database, patients classified as N0 had fewer lymph nodes identified than those classified as N1 [7]. Other investigators have reported a strong correlation between the number of lymph nodes examined and number involved [8]. For example, patients who were N0 had a mean lymph node count of 14.2 AE 7.1 whereas the lymph node count was 18.0 AE 9.3 in patients found to have lymph node metastases [9].…”
Section: Extent Of Lymphadenectomy and Accuracy Of Stagingmentioning
confidence: 98%
“…found that 18 LNs should be removed for adequate staging purposes based on data from a single institution study of 336 cases of stage I to stage IV esophageal carcinoma. In a study of 198 cases (also including all tumor and LN stages), Bollschweileret al [22]. suggested that 15 LNs be sampled to minimize misclassification of LN-positive patients.…”
Section: Transhiatal Versus Transthoracic Esophagectomymentioning
confidence: 99%